2019
DOI: 10.1101/766634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion of a non-canonical regulatory sequence causes loss of Scn1a expression and epileptic phenotypes in mice

Abstract: Genes with multiple co-active promoters appear common in brain, yet little is known about functional requirements for these potentially redundant genomic regulatory elements. SCN1A, which encodes the NaV1.1 sodium channel alpha subunit, is one such gene with two co-active promoters. Mutations in SCN1A are associated with epilepsy, including Dravet Syndrome (DS). The majority of DS patients harbor coding mutations causing SCN1A haploinsufficiency, however putative causal non-coding promoter mutations have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 87 publications
(217 reference statements)
0
9
0
Order By: Relevance
“…Spectral analysis was performed in Python using MEG and EEG analysis and visualization (MNE) open-source software, as previously described in ( 59 , 61 ). Frequency bands were defined as delta 0.5–4 Hz, theta 5–9 Hz, alpha 9–12 Hz, beta 13–30 Hz and gamma 30–50 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Spectral analysis was performed in Python using MEG and EEG analysis and visualization (MNE) open-source software, as previously described in ( 59 , 61 ). Frequency bands were defined as delta 0.5–4 Hz, theta 5–9 Hz, alpha 9–12 Hz, beta 13–30 Hz and gamma 30–50 Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Nakayama et al described two cases of Dravet syndrome carrying microdeletions in the SCN1A promoter region that resulted in SCN1A haploinsufficiency and reduced channel protein levels, leading to Dravet Syndrome [143]. Additionally, Haigh and colleagues have shown that mice harbouring deletions in the non‐canonical promoter region of Scn1a , which include the alternative TSS 1b, exhibit a significant reduction in the expression of Scn1a and an epileptic phenotype [144, 145].…”
Section: Evidence Of Non‐coding Variation In the Epilepsiesmentioning
confidence: 99%
“…Transcriptomic datasets generated for this study are available via the Gene Expression Omnibus (GEO) archive under accessions GSE169481 www.ncbi. nlm.nih.gov/bioproject/PRJNA716688 [97] and GSE169485 www.ncbi.nlm.nih. gov/bioproject/PRJNA716683 [98].…”
Section: Supplementary Informationmentioning
confidence: 99%
“…nlm.nih.gov/bioproject/PRJNA716688 [97] and GSE169485 www.ncbi.nlm.nih. gov/bioproject/PRJNA716683 [98]. Differential Hi-C comparisons used GEO accession GSE87112, www.ncbi.nlm.nih.gov/bioproject/PRJNA343608 [39].…”
Section: Supplementary Informationmentioning
confidence: 99%